Bridging behavior science and gaming theory: Using the Intervention Mapping Protocol to design a serious game against cyberbullying. (March 2016) - DeSmet, Ann; Van Cleemput, Katrien; Bastiaensens, Sara; Poels, Karolien; Vandebosch, Heidi; Malliet, Steven; Verloigne, Maïté; Vanwolleghem, Griet; Mertens, Lieze; Cardon, Greet; De Bourdeaudhuij, Ilse
Abstract: Introduction: The Intervention Mapping Protocol (IMP) was applied to the design of a serious game against cyberbullying among adolescents (12–14y). Method: The IMP comprises 6 predefined steps. A systematic review assessed the cyberbullying problem and associated health risks (Step 1). Surveys and focus groups collected information on behavior and its determinants from adolescents (surveys, n = 1979 and n = 453; focus groups, n = 69), parents (surveys, n = 48 and n = 323) and educators (survey, n = 451) (Step 1, 2). Meta-analyses analyzed effective methods for cyberbullying programs and serious games (Step 3). A survey (n = 530) and focus groups (n = 69 adolescents, n = 8 adolescents) assessed preferences and program material appreciation (Step 4). Planned activities for step 5 (implementation) and step 6 (effectiveness) are reported. Results: Targeting positive bystander behavior (defending, reporting and comforting) was chosen as a viable approach to reduce cyberbullying. Bystander behavior differed by context and was predicted most by positive outcome expectations for the victims. Adolescents valued educator and parental support. Predictors for educator behavior and parental support are described. Serious game design was based on effective change methods and features, and took stakeholder and user preferences into account. Conclusion: Findings may aid professionals in evidence- and theory-based design of cyberbullying interventions and serious games. Highlights: The evidence- and theory-based design of an anti-cyberbullying program is presented. Promoting positive bystander behavior may help end cyberbullying and its harm. Behavior change methods need to be balanced with gaming features, based on evidence. User testing is crucial, and amended the program design. The protocol used professional, user, and stakeholder expertise in game design.